2021
DOI: 10.1097/acm.0000000000004120
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Dissemination of a COVID-19 Airway Management Simulation Using a Train-the-Trainers Curriculum

Abstract: Supplemental Digital Content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…Even the training content is limited to the steps of the process of putting on and taking off protective equipment, personnel with a high level of education can combine theoretical knowledge and practice to master the specific steps of putting on and taking off masks, protective clothing, goggles, and visors. 20,21 Highly educated personnel are better able to understand the significance of each step of putting on and taking off protective clothing, and better understand the consequences of putting on and taking off protective clothing incorrectly. As a result, they are better able to prevent mistakes from happening, and better able to accept with remedial measures after mistakes.…”
Section: Discussionmentioning
confidence: 99%
“…Even the training content is limited to the steps of the process of putting on and taking off protective equipment, personnel with a high level of education can combine theoretical knowledge and practice to master the specific steps of putting on and taking off masks, protective clothing, goggles, and visors. 20,21 Highly educated personnel are better able to understand the significance of each step of putting on and taking off protective clothing, and better understand the consequences of putting on and taking off protective clothing incorrectly. As a result, they are better able to prevent mistakes from happening, and better able to accept with remedial measures after mistakes.…”
Section: Discussionmentioning
confidence: 99%
“…Fourteen studies (16%) [54][55][56][57][58][59][60][61][62][63][64][65][66][67] assessed the impact of introducing simulation training into the healthcare sector. These studies primarily targeted clinical procedures and interventions performed on COVID-19 patients in emergency departments or COVID-19 wards.…”
Section: Simulation Trainingmentioning
confidence: 99%
“…In a study conducted in Colombia, 54.5% of participants (n = 33) agreed that a simulated intervention in PPE donning and doffing reduced individual and collective stress [65]. In the United States, a structured train-the-trainer simulation program targeting PPE usage and airway management skills among emergency and critical care physicians significantly increased comfort levels from 2.93 to 4.35 when managing COVID-19 patients [66]. A Saudi Arabian study found that 57.4% of emergency department healthcare professionals felt more comfortable dealing with unstable COVID-19 patients after implementing mock codes (simulation drills) involving PPE use and basic and advanced airway techniques [67].…”
Section: Mitigation and Coping Toolmentioning
confidence: 99%
“…They were actively involved in efforts to optimize triaging of patients, turn emerging evidence into guidelines, and create multidisciplinary teams to improve care. [7][8][9][10] With little preparation, trainees brought their strong work ethic, eagerness to learn, and readiness to question norms to improving systems and those who practice within them. By being involved in firsthand, real-time systemic endeavors, residents contributed to academic health systems while learning how to practice independently within them.Author affiliations and article information are listed at the end of this article.…”
mentioning
confidence: 99%
“…When academic health systems faced unprecedented hospital admissions and rapidly shifting treatment paradigms, frontline residents reliably contributed to improvement endeavors. They were actively involved in efforts to optimize triaging of patients, turn emerging evidence into guidelines, and create multidisciplinary teams to improve care . With little preparation, trainees brought their strong work ethic, eagerness to learn, and readiness to question norms to improving systems and those who practice within them.…”
mentioning
confidence: 99%